The informant eaudiobook - Grippando, James (2016)
FBI Special Agent Victoria Santos is tracking a string of gruesome murders from New York to San Francisco, Miami to Oregon. Meanwhile, Pulitzer Prize-winning Miami Tribune reporter Mike Posten receives a call from a mysterious stranger who claims his mind works so much like the killer's that he can actually predict the next attack: time, place, victim. When the predictions prove true, Mike and Victoria must join forces to find out if this eerie caller is the real psychopath. Putting themselves in the line of fire, they are about to come face-to-face with the reason why their man kills without a conscience—and why it may be impossible to stop him.